2009
DOI: 10.4103/0972-6748.57858
|View full text |Cite
|
Sign up to set email alerts
|

Insight and its relationship with stigma in psychiatric patients

Abstract: Background:The literature on insight has paid insufficient attention to the social experiences that are associated with receiving and endorsing a diagnosis of mental illness. The psychological and behavioral commitments associated with insight extend beyond agreeing with a diagnosis and accepting treatment to include taking on the identity of an individual diagnosed with mental illness. This study sought to examine the relationship between insight and stigma in psychiatric patients.Materials and Methods:Cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Schizophrenia patients with a better insight of illness, measured as clinical insight in the present study, were more likely to have higher internalized stigma. This is consistent with the previous model of insight and self-stigma 31. The results by Lu and Wang30 showed that lack of insight was not correlated with self-stigma in people with schizophrenia (most were inpatients).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Schizophrenia patients with a better insight of illness, measured as clinical insight in the present study, were more likely to have higher internalized stigma. This is consistent with the previous model of insight and self-stigma 31. The results by Lu and Wang30 showed that lack of insight was not correlated with self-stigma in people with schizophrenia (most were inpatients).…”
Section: Discussionsupporting
confidence: 92%
“…The results by Lu and Wang30 showed that lack of insight was not correlated with self-stigma in people with schizophrenia. Another study found that psychiatric patients with insight have a high level of self-stigma compared to those without insight 31…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has highlighted that personal insight is associated with illness severity and poor treatment compliance (Beck, Cavelti, Kvrgic, Kleim, & Vauth, 2011;Lincoln, Lullmann, & Rief, 2007), poor clinical outcomes (Drake et al, 2007;Saravanan 365 et al, 2010), reduced long-term global functioning (Lincoln et al, 2007), higher levels of depressive symptoms (Murri et al, 2015), and higher stigma. For example, Mishra, Alreja, Sengar, and Singh's (2009) cross-sectional study among 100 psychiatric patients (in-patient and out-patient services) found that levels of 370 stigma were higher among those participants who had insight into their illness. The study participants also highlighted that misconceptions about mental health problems trigger public stigma to occur.…”
Section: Discussionmentioning
confidence: 99%
“…[1112131415161718] Some of these studies have discussed the urban-rural differences and male-female differences in the perception and impact of stigma. [121418] Other studies have evaluated the relationship of stigma with insight.…”
Section: Introductionmentioning
confidence: 99%
“…[121418] Other studies have evaluated the relationship of stigma with insight. [13] Studies have also focused on the context, in which stigma is perceived by patients, possible causes for the stigma, experienced stigma, impact of stigma, and correlates of stigma. [111617] It is evident that research on stigma associated with schizophrenia is mostly from southern India.…”
Section: Introductionmentioning
confidence: 99%